Pengaruh Media Sosial Dan Kualitas Pelayanan Terhadap Kepuasan Pengunjung Objek Wisata The Le Hu Garden - Rianto Manurung (Cattleya Darmaya Fortuna, 2021)
North Sumatra has a lot of interesting tourist attractions. Beach, Lake and Mountain Tourism Objects are places that are crowded on weekends in the North Sumatra Region. The Le Hu Garden is one of the tourist attractions in North Sumatra which presents natural beauty in the form of a flower garden. Located in Deli Serdang district and situated on a 3 hectare land area, this place is very spacious and comfortable for tourists who like to take pictures, see the beauty of flowers and family gatherings. This study uses SPSS 20.00 with the indicator variables X1 and X2 are social media and service quality, variable Y is visitor satisfaction. This study took a sample of 25 visitors.